2016
DOI: 10.1080/19420862.2016.1268305
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of ABBV642, a dual variable domain immunoglobulin molecule (DVD-Ig) that potently neutralizes VEGF and PDGF-BB and is designed for the treatment of exudative age-related macular degeneration

Abstract: Exudative age-related macular degeneration (AMD) is the most common cause of moderate and severe vision loss in developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
(58 reference statements)
0
14
1
Order By: Relevance
“…Next, the half-life of 441 in mice was determined, and found to be 45 h (Supplementary Fig. 5b ) and thus comparable to a closely related format, the DVD-IgG, for which the half-life in mice was also reported to be about 67 h 49 .…”
Section: Resultsmentioning
confidence: 73%
“…Next, the half-life of 441 in mice was determined, and found to be 45 h (Supplementary Fig. 5b ) and thus comparable to a closely related format, the DVD-IgG, for which the half-life in mice was also reported to be about 67 h 49 .…”
Section: Resultsmentioning
confidence: 73%
“…Some of these issues evolve from the use of mono-factor therapies, such as anti-VEGF drugs, to address a multifactorial, multi-genetic disease, as is the case of nAMD. In order to improve effectiveness, combination of treatment with other proangiogenic inhibitors as blocking PDGF ( [183,184], clinicaltrials.gov/NCT01940900), steroids, e.g., triamcinolone [185], or AINEs, such as ketorolac [186], and integrin antagonists [187] has been suggested as adjuvants to anti-VEGF regiments. Collectively, these novel therapeutic approaches indicate the need to simultaneously address a multitude of nAMD-associated factors.…”
Section: Addressing Unmet Needs In Namd Treatmentmentioning
confidence: 99%
“…The main pathological change in exudative AMD is the formation of choroidal neovascularization (CNV) in the macular region (1,3,7). Many studies have shown that overexpression of vascular endothelial growth factor (VEGF) plays a decisive role in its pathogenesis (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%